STUDI KELAYAKAN BISNIS UNTUK PENGEMBANGAN USAHA PADA PT TALENTA INTERNATIONAL TOURISM: - Hartanto Ismail, Adrian; Rahmat, Rahmat (ADMIT: Jurnal Administrasi Terapan, 2023)
Opening a branch company is one of the right strategy to expand the business, opening a branch office is able to have a great benefit to scale up the market share itself. But, in developing business there are a lot of things that have to be concerned in order to avoid losses. Therefore, it is necessary to conduct a feasibility study in order the company to avoid risk of losses. This research was conducted at one of the company in Makassar, PT Talenta International Tourism. This research used qualitative methode to describe result in a descriptive way. Data collection techniques in this study are primary data and secondary data, this study was carried out in march 2023 until it was completed. The aspect that will discuss in this study is management aspect, market and marketing aspect, technical aspect, and financial aspect.